Legal problems of using artificial intelligence - Berdiyarova Ж.С.; Saimova Ш.А.; Abdullaeva Д.С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The article examines the legal issues related to the use of artificial intelligence technologies. The purpose of the study is to analyze the main directions of legal regulation of the use of artificial intelligence and to identify ways to improve the current legislation of the Republic of Kazakhstan. The study applies system analysis, comparative legal and formal legal methods, as well as methods of analysis and synthesis. The article demonstrates that the widespread use of artificial intelligence technologies in various spheres of public life creates new directions for legal regulation. The authors analyze the relationship between the use of artificial intelligence and issues of personal data protection, cybersecurity, intellectual property rights, and legal liability. In addition, the article examines the features of legal regulation of artificial intelligence in the Republic of Kazakhstan and notes that the main principles of legal regulation in this field are fixed in the Law of the Republic of Kazakhstan “On Artificial Intelligence”. The article also provides a comparative analysis of international experience, including legal acts of the European Union in the field of artificial intelligence regulation. The research results highlight the need to further improve the legal framework for regulating artificial intelligence technologies, harmonize national legislation with international practice, and develop legal mechanisms ensuring the safe use of artificial intelligence systems.